APPLICATION OF RESTORATIVE JUSTICE TOWARDS PEOPLE OF MISREPENDENT CRIMES: PENERAPAN RESTORATIVE JUSTICE TERHADAP PELAKU TINDAK PIDANA RINGAN - Br Ginting , Miranda (UPMI Proceeding Series, 2023)
The provisions of the Criminal Code regarding the crime of petty theft contain weaknesses in the limitations of light crimes and the amount of fines that can be imposed. To overcome this legal phenomenon, the Supreme Court initiated the issuance of the Republic of Indonesia Supreme Court Regulation Number 02 of 2012 concerning Adjustments to the Limits of Minor Crimes and the Number of Fines in the Criminal Code. (hereinafter referred to as SUPREME COURT REGULATION 02/2012). In an effort to socialize this Court Regulation to all law enforcement officials, a Memorandum of Understanding was carried out involving the Supreme Court, the Ministry of Law and Human Rights, the Attorney General's Office, and the Indonesian National Police (MAHUMJAKPOL), one of which was a discussion on restorative justice (peaceful dispute resolution) through mediation involving perpetrators, victims, families of perpetrators/victims, and related community leaders to jointly seek a fair solution by emphasizing restoration to its original state at the investigation stage by the police and at the trial stage by the judge. The application of restorative justice to the crime of petty theft according to Supreme Court Regulation Number 2 of 2012. However, in the implementation of mediation, an inhibiting factor was found, namely the lack of understanding of the Police investigators about the crime of theft which is classified as a minor crime. There was no confession or statement of guilt from the perpetrator, There is no consent from the victim / family and there is a desire to forgive the perpetrator, there is no support from the local community to carry out a settlement by deliberation and consensus, the perpetrator has never been punished.